THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE ABOUT THE DANGERS OF CIGARETTES AND CARBON MONOXIDE LEVELS OF BREATHING AIR IN STUDENTS FROM A HIGH SCHOOL IN MALANG - Dwi Pratiwi, Suryanti; Agus Setyawan, Ungky; Mafisah, Saidah; Muhammad, Iqbal; Herda Asyari, Claudia; Dini, Zata; Pratiwi, Eka; Lyono, Albert; Delfianto, Dwiroza Delfianto; Nur Hikmah, Naila Nur Hikmah; Suardana, I Made Suardana; Martha , Martha (Journal of Community Health and Preventive Medicine, 2024)
This study aims to analyze the relationship between the level of knowledge about the dangers of smoking and smoking behavior and exposure to cigarette smoke in high school students. This quantitative descriptive research with a cross-sectional design involved 114 students from one Malang Senior High School, with sampling using a simple random sampling method. Using a CO analyzer, data was collected through questionnaires to measure students' knowledge levels and measurements of carbon monoxide (CO) in breathing air. The study results showed that 62% of the respondents were women and 38% were men, with an average age of 16.8 years. As many as 80% of students do not smoke, while the other 20% are active smokers. The average CO level of the students' breath air was 3.34 PPM, with active smokers showing significantly higher CO levels (7.74 PPM) compared to passive smokers (2.06 PPM) and non-smoking students (2.61 PPM). The ANOVA statistical test showed a significant difference in CO levels between groups (p < 0.05). Although the level of students' knowledge about the dangers of smoking was relatively high (average pretest 124), no significant relationship was found between knowledge and smoking behavior (p = 0.802). The study concluded that although knowledge about the dangers of smoking is moderate, smoking behavior among male students remains high, suggesting the need for more in-depth interventions to address the social and psychological factors that support smoking behavior.